Comparative efficacy of intra-articular hyaluronic acid and corticosteroid injections in the management of knee osteoarthritis - Kushwaha, Narendra Singh; Chauhan, Pushprajan; Verma, Ashutosh; Kaushal, Rajan Kumar; Patel, Mohit Kumar; Kumar, Shambhu (International Journal of Research in Orthopaedics, 2023)
Background: Osteoarthritis management includes a myriad of treatment modalities. This study compared the effects of corticosteroid and Hylan G-F 20 injections on knee osteoarthritis outcomes. Methods: Patients were randomized to receive either corticosteroid or Hylan G-F 20 injections. Outcome measures included the Western Ontario and McMaster Universities Osteoarthritis Index, knee society rating system scores, and visual analog scale scores, collected at baseline, 3 months, and 6 months. Results: Baseline demographic and clinical parameters were comparable between both groups. The corticosteroid group demonstrated a significant decrease in the WOMAC score over time (p<0.001). Hylan G-F 20 group showed significant improvements in both the WOMAC scores and Visual Analog Scale scores over time (p<0.01). Gender-based sub-analysis suggested both treatments were effective in men, while in women, significant benefits were seen only with Hylan G-F 20. Conclusions: Both corticosteroid and Hylan G-F 20 demonstrated efficacy in managing knee osteoarthritis, albeit in different domains. The results suggest the need for individualized treatment plans and further research into potential gender-based variations in treatment response.